Wight Family History Folder - Grady County Historical Society (My University, 1845)
The folder contains a detailed history of the Wight family. Included in the folder are handwritten and typed letters. These letters discuss the early founding and role the Wight family played in the founding of Cairo.
This item includes 1 PDF file with 84 JPGs.
Keywords: Grady County (Ga.); Cairo (Ga.); Correspondence